2012
DOI: 10.20452/pamw.1284
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume as an inflammatory marker in acute exacerbation of chronic obstructive pulmonary disease

Abstract: IntroductIon Mean platelet volume (MPV) is inversely correlated with inflammation in inflammatory bowel diseases, rheumatoid arthritis, and ankylosing spondylitis as shown in the previous studies. It has been reported that elevated values of MPV are associated with cardiovascular diseases and stable chronic obstructive pulmonary disease (COPD). However, MPV values in acute exacerbation of COPD have not been investigated so far.objectIves This retrospective study was conducted to investigate the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
76
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 36 publications
8
76
0
6
Order By: Relevance
“…With regard to the changes in mean platelet volume levels, our findings are in line with the results of a study by Ulasli et al, 10 who demonstrated that in the exacerbation period of COPD, mean platelet volume levels were decreased. On the contrary, they failed to detect a correlation between mean platelet volume and C-reactive protein, probably due to their small sample size, the baseline increased level of C-reactive protein, or the high mean platelet volume levels in the stable period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to the changes in mean platelet volume levels, our findings are in line with the results of a study by Ulasli et al, 10 who demonstrated that in the exacerbation period of COPD, mean platelet volume levels were decreased. On the contrary, they failed to detect a correlation between mean platelet volume and C-reactive protein, probably due to their small sample size, the baseline increased level of C-reactive protein, or the high mean platelet volume levels in the stable period.…”
Section: Discussionsupporting
confidence: 92%
“…15,16 In our study, WBC count and the percentage of neutrophils were significantly higher compared with during the stable period, as were the C-reactive protein levels, although not normalized, as expected. 16 The investigators of the above studies 10,11 favor this view. However, the intensity of inflammation during COPD exacerbation could lead to reverse results (ie, increased mean platelet volume).…”
Section: Discussionmentioning
confidence: 98%
“…However, there was no correlation between logarithmic values of MPV, CRP and platelet values in patient groups. Yuksel et al, Ulaslı et al, as well reported that no correlation was observed between CRP and MPV in patients with ulcerative colitis and chronic obstructive pulmonary disease, respectively 8,27 . The findings of our study were in line with the results of these previous studies.…”
mentioning
confidence: 98%
“…Additionally, higher MPV correlates well with an increased number of platelet-platelet aggregates, and the elevated MPV values are linked with a shortened bleeding time, increased thromboxane A2 and B2 per unit volume and expression of the large amount of adhesion molecules, such as P-selectin glycoprotein 1b and glycoprotein IIb/IIIa (10). Larger platelets are probably younger, more reactive, and create more thrombogenic factors (11). Therefore, large platelets are more agreeable and, metabolically and enzymatically more active compared to small platelets and normal platelets (12).…”
Section: Discussionmentioning
confidence: 99%